Development of near-infrared chemiluminescent probes for in vivo imaging - Huang, Jingsheng (Nanyang Technological University, 2022)
Molecular imaging is an indispensable tool in deciphering and monitoring the physiological and pathological processes at the subcellular or cellular level. For visualization and quantification of biological processes, multiple imaging modalities are developed along with different image-capture techniques, including ultrasound (US), computed tomography (CT), magnetic resonance (MRI), and positron emission tomography (PET) technologies. Among these different imaging modalities, optical imaging outperforms others in the high-throughput capacity, less radiative toxicity, and low-cost equipment. Moreover, in contrast to anatomical imaging and biopsy imaging, optical real-time imaging shows great advantages in time-consuming, high resolution, and noninvasiveness without pain for diagnosis and treatment in the clinic. There are two types of optical imaging agents, namely inorganic and organic imaging agents. Inorganic agents always suffer from biotoxicity resulting from leakage of metal ions and difficult biodegradability, which impede their further application in translational applications. Organic optical agents exhibit an excellent sensitivity for biomarker detection at the subcellular levels, facilitating both pre-clinical and clinical applications. Despite these merits, optical imaging is still confronted with narrow penetration tissue depth (< 1 cm) and compromised imaging quality (low signal-to-background ratio, SBR) because of tissue autofluorescence caused by real-time excitation. To address the mentioned issues, other novel imaging modalities have been developed, especially second near-infrared-II (NIR-II) fluorescence imaging and chemiluminescence (CL) imaging. NIR-II fluorescence imaging is booming along with the development of emerging NIR-II Imaging techniques in recent years. NIR-II fluorophores (emission wavelength: 1,000-1,700 nm) exhibit superior optical properties owing to diminished background autofluorescence and reduced light scattering. Unfortunately, NIR-II fluorophores always suffer from low fluorescence quantum yield and show difficulties in the design of activatable probes, causing low SBR because of the “always-on” signal. Interestingly, chemiluminescence imaging can offer another strategy to overcome these issues because chemiluminescence has a different work mechanism (Chemically Initiated Electron Exchange Luminescence, CIEEL) which is light emission from a chemical reaction without real-time excitation, exhibiting well-performed tissue penetration and high SBR. Compared with NIR-I/II fluorescence imaging, CL imaging shows great superiorities in tissue penetration depth and SBR. All of our works are carried out for bioimaging and sensing through the modification of Schaap’s adamantylidene−dioxetane scaffold. Because Schaap’s chemiluminophores are an attractive chemiluminescent scaffold due to the relative thermal stability of dioxetane and good response-ability to detect biological markers.